Electrochemical application of Ga2O3 and related materials: CO2-to-HCOOH conversion. (25th August 2016) - Sekimoto, Takeyuki; Hashiba, Hiroshi; Deguchi, Masahiro; Yotsuhashi, Satoshi; Masui, Takekazu; Kuramata, Akito; Yamakoshi, Shigenobu
Abstract: We report on the complex catalytic behavior of Ga2 O3 for the electrochemical reduction of CO2 to formic acid (HCOOH). Although the experiments were reproducible, the behavior observed during the reaction was complex. A characteristic feature of the reaction was that Faradaic efficiency was strongly dependent on the electric charge during electrolysis. This result implied that the produced HCOOH affected the CO2 reduction reaction on the surface of the electrode, which was confirmed by experiments with initially added acid. The Faradaic efficiency for HCOOH production (η_HCOOH ) increased with electric charge, and was further increased by the presence of initially added acid. We also show electrochemical CO2 reduction over other Ga compounds such as GaN and GaP, for which it can be assumed that p electrons and the Ga–Ga distance on the surface of the catalyst have important roles in selective HCOOH production as in the case of Ga2 O3 .